Omnibus Law Cipta Kerja Dan Prospek Ketahanan Pekerja Migran Indonesia - Aswindo, Munarni; Ras, Abdul Rivai (UI Scholars Hub, 2020)
Since it was officially promulgated on November 2, 2020, the presence of the Omnibus Law on Job Creation has repealed two regulations and amended at least 80 (eighty) other laws. Particularly in the labor cluster, four laws are affected, including regulations related to Migrant Workers, which have not been widely explained. This study aims to explain the dynamics of the Indonesian Migrant Workers (IMW) regulatory policy and several problems in the omnibus law on Job Creation. To further analyze and describe the implications of the Omnibus law on the prospects for PMI resilience. As a policy study, this research uses secondary data in the form of statutory regulation and literature. The data were analyzed using conceptual and normative approaches which were presented in a descriptive-qualitative manner. The results showed that IMW's regulatory policies included international policies that emphasized the recognition of migrant workers' rights. Meanwhile, at the national level, IMW protection policies have been regulated in a specific law which over time has become more accommodating to their interests. However, the presence of the Omnibus law has changed and loosened the licensing provisions for Indonesian Migrant Worker Placement Companies (P3MI) in the law, which has an impact on IMW's vulnerability. So that instead of being progressive, the omnibus law on Job Creation brings the prospect of resilience to Indonesian migrant workers in a degressive direction. Keywords: Omnibus Law, Migrant Workers, Worker’s Right, Protection, Resilience